Feasibility Study of a Novel Open Ocean Aquaculture Ship Integrating with a Wind Turbine and an Internal Turret Mooring System - Hanyu Liu; Mingsheng Chen; Zhaolong Han; Hao Zhou; Lin Li (Journal of Marine Science and Engineering, 2022)
Marine aquaculture has been expanded into more remote areas due to the increasing demand for high value-added fish products, bringing more challenges in fuel supply and mooring safety to open ocean aquaculture farms. Therefore, the idea of integrating aquaculture farms with offshore renewable energy has attracted tremendous interest. This study proposes a novel open ocean aquaculture ship integrated with a NREL 5 MW wind turbine. In addition, an internal turret mooring system is installed at the bow of the aquaculture ship, making the wind turbine always face the wind blowing direction due to the weathervaning effect. In this study, a preliminary study of the dynamics and wind power generation of the proposed open ocean aquaculture ship was conducted. The aerodynamic and elastic effects of the wind turbine and the effect of nets under the wave and current behavior on the dynamics of the single-point moored aquaculture ship were investigated. Furthermore, the effects of the dynamics of the aquaculture ship on the power generation of the wind turbine were also studied to investigate the feasibility of the idea to integrate an aquaculture ship with a wind turbine.